Pembelajaran mod meradun derasaskan modul interactive lecture dalam kalangan pelajar (Blended learning mode based on interactive lecture module among students) - Sankaran, Surendran; Saad, Norazlinda (UUM Press, 2019)
The purpose of this study is to identify the relationship between Design Dimension, Evaluation of Educators Dimension, Content Dimension and Evaluation Dimension with Blended learning mode based on Interactive Lecture Module among students who are taking Computer Applications in Bahasa Melayu. The quantitative research approach in this study is descriptive using the survey method. The population of this research is students who are taking Computer Applications in Bahasa Melayu. The purposeful sampling was used to obtain a group of respondents who have certain characteristics according to the requirements of the study. A total of 243 students was selected as the study sample. In the pilot study, several aspects of item adjustment were carried out resulting in a high Cronbach Alpha value (0.89). The collected data were analyzed using descriptive statistics and Pearson correlations. The findings of the study indicate that there is a significant relationship between the Design Dimension, Evaluation of Educators Dimension, Content Dimension and Evaluation Dimension with Blended learning mode based on Interactive Lecture Module among students who are taking Computer Applications in Bahasa Melayu. The findings explain that in order to increase the level of Blended learning mode based on Interactive Lecture Module among students, the Design Dimension, Evaluation of Educators Dimension, Content Dimension and Evaluation Dimension need to be enhanced.